The Zygotic Division Regulator ZAR1 Plays a Negative Role in Defense Against Botrytis cinerea in Arabidopsis - Chen, Lijuan; Xiao, Jiahui; Song, Yuxiao; Li, You; Liu, Jun; Cai, Huiren; Wang, Hong-Bin; Liu, Bing (Frontiers in Plant Science, 2021)
A phosphorylation/dephosphorylation cycle at tyrosine 428 of CHITIN ELICITOR RECEPTOR KINASE 1 (CERK1) plays an essential role in chitin triggered immunity in Arabidopsis thaliana. In this study, we used a differential peptide pull-down (PPD) assay to identify factors that could participate downstream of this cycle. We identified ZYGOTIC ARREST 1 (ZAR1) and showed that it interacts with CERK1 specifically when the tyrosine 428 (Y428) residue of CERK1 is dephosphorylated. ZAR1 was originally characterized as an integrator for calmodulin and G-protein signals to regulate zygotic division in Arabidopsis. Our current results established that ZAR1 also negatively contributed to defense against the fungus Botrytis cinerea and played a redundant role with its homolog ZAR2 in this process. The zar1-3 zar2-1 double mutant exhibited stronger resistance to B. cinerea compared with zar1-3 single mutant, zar2-1 single mutant, and wild-type plants. Moreover, the inducible expression of numerous defense response genes upon B. cinerea infection was increased in the zar1-3zar2-1 double mutant, consistent with a repressive role for ZAR proteins in the defense response. Therefore, our findings provided insight into the function of ZAR1 in multiple defenses and developmental regulation pathways.